Discriminatory language in the workplace: unmasking prejudices and stereotypes - Di Marco, D.; Arenas, A.; Munduate, L.; Hoel, H. (Revista de Psicologia Social, 2019)
The link between language, communication and open discrimination has been the focus of numerous studies. For many years, language has been a vehicle of prejudice and negative stereotypes. However, in the last few years, overt verbal aggressions have diminished thanks to the implementation of equality policies and awareness-raising initiatives. Despite that, negative attitudes against protected groups might not have disappeared and may instead be transmitted subtly, such as through uncivil language. The goal of this research is to study the relation between language and subtle discrimination against lesbian and gay (LG) workers. With this goal in mind, 39 in-depth interviews were conducted. The analysis showed that LG people are victims of subtle discrimination and that language is one of the most common vehicles of prejudice and negative stereotypes. Jokes, inappropriate comments and questions are the expression of negative attitudes, which are probably present at an implicit level. Due to the ambiguity of these expressions and the settings where they have been studied — the workplace — these acts could be defined as uncivil behaviours. Practical implications, limitations and directions for future research are discussed.